The Role of Transformational Leadership in Strategic Containment: An Analytical Study of the Views of Academic and Administrative Leaders in Private Universities in the Kurdistan Region of Iraq - Abdullah Kak ahmed, Zainab; Maroof Jameel, Parishan (Iraqi Journal for Administrative Sciences, 2026)
The study aims to examine the nature of the relationship and the effect between transformational leadership and its dimensions as an independent variable, and strategic containment and its dimensions as a dependent variable in private universities in the Kurdistan Region of Iraq. The research problem emerged from questions concerning the extent to which transformational leadership practices contribute to enhancing the ability of private universities to adapt to environmental changes and implement their strategies efficiently. The study adopted the descriptive analytical approach and used a questionnaire as the main instrument for data collection. The research sample was selected using a purposive sampling method to ensure adequate representation of influential leadership levels. The sample comprised 199 academic leaders from 16 private universities in the Kurdistan Region of Iraq. The research hypotheses were statistically tested using the SPSS V.24. The results of the statistical analysis revealed a strong and positive correlation and a significant effect of transformational leadership in enhancing strategic containment. Accordingly, the study recommends strengthening transformational leadership practices in a more systematic manner through specialized leadership training and development programs, in order to support strategy implementation and achieve institutional sustainability.